G59(P) Long-Term Psychological and Social Impact Reported by Childhood Critical Illness Survivors: A Systematic Review and Thematic Synthesis. (4th June 2013) - Manning, JC; Hemingway, P; Redsell, S
Abstract : Aims: Over 250, 000 children annually in the US and UK experience critical illnesses. Advances in medicine and care have significantly reduced mortality, with over 95% of patients that survive. However, the long term psychological and social impact, as reported by children and adolescents that survive critical illness, is unclear. This paper reports a systematic review and thematic synthesis of qualitative literature that aims to explore and understand these phenomena. Methods: CINAHL; MEDLINE; PMC; PsychINFO; ASSIA and Dissertation and Thesis Databases were searched between 1806 and February 2012. Studies were selected using eight predetermined criteria (e.g. only qualitative empirical studies) and methodological quality was assessed using two standardised checklists (1, 2). Thematic synthesis (3) was used to extract, code and synthesise data. Results: From the 1307 studies identified, three met the inclusion criteria which were all of moderate methodological quality. All included studies were conducted in the UK involving a total of 51 participants aged 1–25 years. Reasons for participant critical illness were predominantly due to head/spinal injury, sepsis, or malignancies. Eighty-six codes and six novel themes emerged from the data. Themes included: confusion and uncertainty; other people's narratives; focus on former self and normality; social isolation and loss of identity; transition and transformation. Analytical synthesis culminated in a framework which attempts to conceptualise the childhood survivors' journey. Conclusions: Childhood critical illness can expose survivors to a complex trajectory of recovery with residual psychosocial adversity manifesting in the long-term. Health professionals need to comprehend and support the potential complex psychological and social needs that may occur. Further empirical research is required to explore and test the conceptual framework developed from this thematic synthesis. References: Walsh D, Downe S. Appraising the quality of qualitative research. Midwifery . 2006; 22:108–19. Thomas J, Sutcliffe K, Harden A, et al. Children and Healthy Eating: A systematic review of barriers and facilitators. London: EPPI-Centre, University of London 2003. Thomas J, Harden A, Oakley A, et al. Integrating qualitative research with trials in systematic reviews. BMJ . 2004; 328 :1010–2.